Implimentasi sifat sarkastik terhadap perwatakan Totan dan Pengarang dalam pementasan teater Setor-P / Hidayah Mohd Najid Shauqi - Mohd Najid Shauqi, Hidayah (Faculty of Film, Theatre and Animation, 2013)
Sarcastic a figure of speech in which the meaning that is communicated is the opposite of the meaning that would be communicated if used literally. This trait can be seen among peers and among close friends. This study was performed to inject sarcastic nature into Totan’s character and The Author in the theater Setor-P. Totan’s character is one of the main characters in this theater. Sarcastic nature can enhance and highlighting Totan and The Autor’s character in this play. I used The Stanislavski System to get a clear picture of how sarcastic it is served. Application of this nature is done in the training process until the last stage. The findings can be seen after researchers understand the meaning of sarcastic and implement itself into the character that will be played. The concept of this play is naturalism and as an actor, I used indicators and methods of the System.